2008
DOI: 10.1111/j.1365-2915.2008.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced susceptibility to DDT in field populations of Anopheles quadriannulatus and Anopheles arabiensis in Malawi: evidence for larval selection

Abstract: Bioassays for insecticide resistance in adult mosquitoes were conducted on samples of Anopheles gambiae Giles s.l. (Diptera: Culicidae) species collected as larvae from breeding sites in the lower Shire Valley, Malawi. The results indicate full susceptibility to permethrin, deltamethrin and malathion, but reduced susceptibility to DDT in one sample from Thom (LT(50) of 8.39 min for females and 25.09 min for males). Polymerase chain reaction-based species identification of the mosquitoes assayed revealed a mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
(28 reference statements)
2
22
0
Order By: Relevance
“…Since travel is also associated with malaria illness in this study, it is possible that LLINs were not used during travel, hence decreasing their effectiveness in preventing malaria illness. The lack of effectiveness also raises the possibility that insecticide resistance, which has been well documented in Malawi [3032], could be contributing. More research on the role of insecticide resistance on LLIN effectiveness in the urban and peri-urban setting will help address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Since travel is also associated with malaria illness in this study, it is possible that LLINs were not used during travel, hence decreasing their effectiveness in preventing malaria illness. The lack of effectiveness also raises the possibility that insecticide resistance, which has been well documented in Malawi [3032], could be contributing. More research on the role of insecticide resistance on LLIN effectiveness in the urban and peri-urban setting will help address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study carried out in Chikwawa district showed that An. arabiensis was completely susceptible to both pyrethroids (permethrin and deltamethrin) [30]. While insecticide resistance appears to be increasing, the overall trends are less striking compared to An.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier results obtained from Chikwawa showed moderate resistance to DDT by An. arabiensis populations [30] and it was speculated that there could be selection occurring at larval stage against DDT derivatives that might still be present in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Field testing of the VPMT by ourselves and others has taken place in Malawi and South Africa, and VPMT protocols are now being used routinely to support interventions in Equatorial Guinea and southern Africa and for other studies [3740]. Feedback from end users has enabled us to develop additional guidelines and advice.…”
Section: Feedback From Field Testingmentioning
confidence: 99%